Pengaruh sistem informasi akuntansi dan sistem pengendalian internal terhadap kinerja karyawan - Wijaya, Dimas Azharino; Priono, Hero (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to obtain empirical evidence of the effect of accounting information systems and internal control systems on employee performance. This study uses quantitative research methods. The object of this research is Perumda BPR Bank Daerah Lamongan with the number of employees who can be used as respondents as many as 34 people. The results of the study indicate that the accounting information system has a positive and significant effect on employee performance so that these results are in accordance with the hypothesis proposed in the study. The internal control system has a positive and significant effect on employee performance so that these results are in accordance with the hypothesis proposed in the study. The value of the coefficient of determination (R Square) is 0.837, which means that 83.7% of the variation of the accounting information system and internal control system variables can explain the employee performance variable, while the remaining 16.3% is explained by other independent variables not proposed in the research model.